Research on the application of non-contact continuous vital signs monitoring in the assessment of patients with chronic obstructive pulmonary disease - LIU Shuang, LONG Zhicong, ZHOU Yuqi, LUO Yinghua, YANG Hailing (Xin yixue)
ObjectiveTo evaluate the clinical application value of non-contact vital signs monitoring in patients with chronic obstructive pulmonary disease （COPD）， analyze the correlation between multi-dimensional vital signs parameters and disease severity， and explore their application value in COPD monitoring. Methods A total of 55 COPD patients treated at the Tianhe Campus of the Third Affiliated Hospital of Sun Yat-sen University from March 2021 to October 2023 were enrolled. All patients underwent deployment of a novel non-contact vital signs monitoring system and completed standardized pulmonary function assessments. Clinical baseline data were collected， and nocturnal physiological signals were recorded， with core monitoring indicators including heart rate variability （HRV）， respiratory characteristics， and sleep structure. Based on pulmonary function assessments， patients were categorized into mild， moderate， severe， and very severe groups. The mild cases were classified as the non-severe group， while the moderate， severe， and very severe cases were combined into the severe group. Intergroup differences were compared， a risk model was constructed， and the efficacy of each parameter in assessing COPD severity was analyzed using receiver operating characteristic （ROC） curves. Results Significant differences were observed among the mild， moderate， severe， and very severe cases in terms of gender， age， body mass index （BMI）， forced expiratory volume in the first second （FEV1）， forced vital capacity （FVC）， and FEV1/FVC ratio （all P < 0.05）. Significant differences were also found between the two groups in total cardiac energy， total cardiac energy baseline value， sympathetic nerve tension index， sympathetic nerve tension baseline value， vagal nerve tension index， and vagal nerve tension baseline value （ all P < 0.05）， with these indicators showing an increasing trend as disease severity worsened. No significant differences were observed in autonomic nerve balance and autonomic nerve balance baseline value between the groups （all P > 0.05）. HRV had a notable impact on COPD severity. The vagal nerve tension index， total cardiac energy baseline value， light sleep duration， and long-term baseline respiratory parameters demonstrated high efficacy in diagnosing disease severity， with areas under the ROC curve （AUC） values of 0.892， 0.886， 0.800， and 0.733， respectively. Conclusions Non-contact continuous vital signs monitoring is feasible in the management of COPD. Indicators such as HRV， light sleep duration， and long-term baseline respiratory rate hold significant clinical value in the monitoring and assessment of COPD patients.